Blood, Cellular, and Tissular Calcineurin Inhibitors Pharmacokinetic–Pharmacodynamic Relationship in Heart Transplant Recipients: The INTRACAR Study. Issue 2 (April 2023) - Coste, Gwendal; Chabanne, Céline; Tron, Camille; Lelong, Bernard; Verdier, Marie-Clémence; Roussel, Mikael; Le Gall, François; Turlin, Bruno; Desille-Dugast, Mireille; Flécher, Erwan; Laviolle, Bruno; Lemaitre, Florian
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: After heart transplantation, calcineurin inhibitors (CNI) (cyclosporin A and tacrolimus) are key immunosuppressive drugs to prevent graft rejection. Whole-blood concentration (Cblood )-guided therapeutic drug monitoring (TDM) is systematically performed to improve graft outcomes. However, some patients will still experience graft rejection and/or adverse events despite CNI Cblood within the therapeutic range. Other pharmacokinetic parameters, such as the intragraft, or intracellular concentration at the CNI site of action could refine their TDM. Nonetheless, these remain to be explored. The objective of the INTRACAR study was to describe the relationship between whole blood, intragraft, and intracellular CNI concentrations as well as their efficacy in heart transplant recipients (HTR). Methods: In a cohort of HTR, protocol endomyocardial biopsies (EMB) were collected to assess rejection by anatomopathological analysis. Part of the EMB was used to measure the intragraft concentrations of CNI (CEMB ). Cblood and the concentration inside peripheral blood mononuclear cells, (CPBMC ), a cellular fraction enriched with lymphocytes, were also monitored. Concentrations in the 3 matrices were compared between patients with and without biopsy-proven acute rejection (BPAR). Results: Thirty-four HTR were included, representing nearly 100 pharmacokinetic (PK) samples for each CNI. Cblood, CEMB, and CPBMC correlated for both CNI. BPAR was observed in 74 biopsies (39.6%) from 26 patients (76.5%), all except one was of low grade. None of the PK parameters (Cblood, CEMB, CPBMC, CEMB/blood, and CPBMC/blood ) was associated with BPAR. Conclusions: In this cohort of well-immunosuppressed patients, no association was observed for any of the PK parameters, including Cblood, with the occurrence of BPAR. However, a trend was noticed for the CEMB and CEMB/blood of cyclosporin A. Further studies in higher-risk patients may help optimize the use of CEMB and CPBMC for CNI TDM in HTR.